Bringing Student Responsibility to Life: Avenues to Personalizing High Schools for Student Success. Issue 3 (3rd July 2017) - Torre Gibney, Daniela; Preston, Courtney; Drake, Timothy A.; Goldring, Ellen; Cannata, Marisa
ABSTRACT: This study examines how school structures and policies shape school culture to ultimately influence student success in one urban high school. We develop a model that explains how caring and personalized connections between students and teachers, coupled with a focus on academic press and support, interact with teacher efficacy to influence student self-efficacy, student attachment to school, and ultimately greater student achievement. We collected data through focus group and individual interviews with students, teachers, and leaders, classroom observations, and school artifacts. Data were analyzed using the constant comparative method allowing for the emergence of important patterns. The data revealed several interrelated structures and processes that support teacher and student efficacy and ultimately instill in students a responsibility for their own learning. This case study highlights the need for administrators to develop buy-in from teachers around a cohesive vision in order for structural reforms to be effective.